Evaluation of a police training on de-escalation with trauma-exposed youth. (September 2021) - Mehari, Krista R.; Rodgers, Caryn R.R.; Blanton, Megan A.; Turner, Lisa A.
Abstract : This study reports the development and evaluation of a police training workshop on de-escalating situations with trauma-exposed youth. The training was developed using a participatory action framework, with the goal of increasing knowledge of adolescent development and the impact of trauma, and promoting skills for de-escalating situations with adolescents. A mixed methods study was conducted to explore the effectiveness of the workshop. Participants were 98 current police officers and recruits. Following the training, knowledge about adolescents and self-efficacy for dealing with adolescents increased, and anxiety about working with adolescents decreased. Open-ended responses indicated that the training was well received. A brief intervention can promote police officers' knowledge of adolescents, self-efficacy, and ease in interacting with adolescents. Future research should build on these findings to determine if these changes lead to a decrease in the use of force in interactions with adolescents. Highlights: Police officers respond to a range of discretionary situations involving youth. A brief training can increase officers' knowledge and self-efficacy and decrease anxiety. Officers appreciate the opportunity to learn from their peers. Hands-on training and coaching is likely necessary to promote skill use.